Hadis Tematik Politik Pemerintahan - Yoan Febriawan; Abustani Ilyas; Tasbih (Aksioreligia, 2026)
This study examines the concept of governmental politics from the perspective of the hadiths of prophet muhammad (pbuh) by employing a thematic hadith approach and analyzing the relevance and implementation of its political values within contemporary state governance. As the second primary source of islamic teachings after the qur’an, the prophetic hadith provides normative and ethical foundations concerning leadership, authority, justice, trustworthiness (amanah), consultation (shūrā), and the responsibilities of rulers toward their citizens. Through the thematic hadith approach, this study systematically compiles and analyzes hadiths related to governmental politics, thereby generating a comprehensive and holistic understanding of the subject. The findings reveal that governmental politics in islam is not perceived as a means of pursuing power, but rather as a trust that must be exercised in accordance with the principles of justice, integrity, and public welfare (maṣlaḥah). These values demonstrate strong relevance to contemporary governance practices, particularly in addressing issues such as corruption, abuse of power, weak bureaucratic integrity, and legal injustice. The implementation of the prophetic values contained in the hadiths can be realized through the strengthening of political ethics, the promotion of good governance, the enhancement of public participation, and exemplary leadership. Therefore, the thematic study of hadith makes a significant contribution to the formulation of a contextual and applicable islamic political ethics framework aimed at fostering a just, transparent, and welfare-oriented government.